2019
DOI: 10.2337/dc18-2029
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Cardiovascular Risk Profile From Childhood to Midlife Between Individuals Who Did and Did Not Develop Diabetes at Follow-up: The Bogalusa Heart Study

Abstract: Childhood and young adulthood may represent time periods in which cardiovascular risk factors (CVRFs) and their cumulative exposure lay the foundation for future risk of chronic diseases. We examined the longitudinal burden of CVRFs since childhood in men and women in whom diabetes did and did not develop at follow-up. RESEARCH DESIGN AND METHODS We included 1,530 participants (mean [SD] follow-up time 33.1 [8.2] years), who participated in the Bogalusa Heart Study and had been examined at least four times sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 36 publications
3
26
0
Order By: Relevance
“…Type 2 diabetes has been shown to be associated with adverse differences in cardiovascular risk factor levels, which in line with our findings, are more pronounced in women than in men 4–7 26. Correspondingly, BMI and waist circumference differ more between women with and without diabetes than between men with and without diabetes 7 26.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Type 2 diabetes has been shown to be associated with adverse differences in cardiovascular risk factor levels, which in line with our findings, are more pronounced in women than in men 4–7 26. Correspondingly, BMI and waist circumference differ more between women with and without diabetes than between men with and without diabetes 7 26.…”
Section: Discussionsupporting
confidence: 90%
“…To our knowledge, sex differences associated with oral glucose tolerance test (OGTT) based pre-diabetes and continuous HbA1c among individuals without type 2 diabetes have not been reported previously. However, longitudinal studies did focus on sex differences related to the conversion to diabetes or dysglycemia 24–26. These studies found that women who eventually developed diabetes experienced a greater deterioration in fasting plasma glucose, lipid levels, and BMI during their non-diabetic state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, women may experience a prolonged state of insulin resistance and metabolic dysfunction prior to diagnosis with type 2 diabetes [15,81]. This theory is supported by the Bogalusa Heart Study's findings that women diagnosed with type 2 diabetes as adults have a greater cumulative exposure to cardiovascular risk factors over their lifetime, starting in youth [82]. For instance, sex CV, cardiovascular; IR, insulin resistance; IUGR, intrauterine growth restriction; T2D, type 2 diabetes differences in endothelial dysfunction are a potential biological mediator of the excess vascular risk observed in women with diabetes [83,84].…”
Section: Potential Mechanisms For the Observed Sex Difference In The mentioning
confidence: 99%
“…Only four studies investigated the effect of treatment with metformin to prevent T2DM, and these studies showed a RR of 0.74 (95% CI, 0.6-0.8), resulting in a number needed to treat of 14 (95% CI, [10][11][12][13][14][15][16][17][18][19][20][21][22]. Although effective, the two studies providing a direct comparison between lifestyle intervention and metformin showed that lifestyle intervention was more effective than metformin, albeit with a small difference in the Indian Diabetes Prevention Program (DPP).…”
Section: Management Of Pre-diabetesmentioning
confidence: 99%